Da Cabala à dança: uma etnografia da oração corporal malachim - COSTA, Ana Claúdia Pinto da (2014)
This research investigated through the theoretical and methodological field of Anthropology of Dance, the Body Prayer Malachim, in order to understand and reveal their ritual structure, its symbolism and its implicit cosmology. The Malachim dance is a contemporary choreography, included in the repertoire of twelve dances from original work of Frida Zalcman entitled Hebrew Dances of Praise, inspired by a set of prayers sung in Jewish Congregation of Brazil, in Rio de Janeiro. Transformed into veritable prayers in motion, are danced in several groups of Sacred Circle Dances, both in Brazil and abroad. The research is part of a broader study about the Body Prayers, guided in this particular case, by the precepts of Kabbalah, the Tree of Life, taking into consideration the four worlds and their energy emanations (Sefirot). Hypothetically the Sacred Circle Dances can work as a kind of tool of physical, mental, emotional and spiritual healing, thanks to its sacredness, strongly present in every movement performed. This is a qualitative ethnographic research, whose fieldwork was conducted in Belém do Pará, in August 2013, when Frida Zalcman gave a workshop at the “School of Theatre and Dance” at the Federal University of Pará (ETDUFPA). Hopefully, with this research, other studies might emerge to investigate this dance form, further expanding their understanding as well as their inclusion in available bibliography from Sacred Circle Dances.